Trajectory planning and motion control of full-row seedling pick-up arm - Ren, Ling; Wang, Ning; Cao, Weibin; Li, Jiangquan; Ye, Xingchen (International Journal of Agricultural and Biological Engineering, 2020)
Frequent start-stops of automatic seedling transplanters would lengthen the seedling picking time due to alternating movement of the motor, and cause positioning errors and frequent motor vibrations when starting the machine. To solve these problems and ensure the pick-up continuity of automatic transplanters, in this study the smooth circular arc interpolation algorithm and the least square method for multinomial curve fitting were used to conduct the trajectory planning of automatic transplanter based on the movement of the pick-up arm of the transplanter. Velocity and time curves were fitted in segments to acquire motion control parameters and further tracking control was conducted. The mathematical model of the control system was established using Simulink, and simulation analysis and system debugging test were performed. Experiments show that the trajectory curves obtained by MATLAB’s data processing can realize the continual and smooth motion trajectory of the pick-up arm; stepper motor velocity control can effectively track the planning curve and improve the seedling pick-up efficiency. The pick-up and pushing time of each motion of the planned plug seedling transplanter reduced by 1.0678 s and the start-stop times reduced from 6 to 1, which solved the frequent motor vibrations when starting the machine and improved the stability of the system. In addition, overstep and out-of-step of the motor at the start-stop moment were avoided and displacement error was reduced. Keywords: trajectory planning, motion control, motion trajectory simulation, transplanter, stepper positioning DOI: 10.25165/j.ijabe.20201303.5264 Citation: Ren L, Wang N, Cao W B, Li J Q, Ye X C. Trajectory planning and motion control of full-row seedling pick-up arm. Int J Agric & Biol Eng, 2020; 13(3): 41–51.